International research output of the University of Sri Jayewardenepura – a Scientometric study - Arulanantham, S.; Navaneethakrishnan, S. (University of Sri Jayewardenepura, 2013)
One of the key areas for the enhancement of development of Sri Lankan higher education is improving productivity in research activities at University level. The systematic and potential visual representations of bibliometric findings can ultimately facilitate the development of a mental model of the research structure and new research activities of an institution at international level and they should be encouraged to evaluate research performance of an institution in a country. Accordingly this study was undertaken a bibliometric investigation of the International research output of the University of Sri Jayewardenepura, one of the ancient Universities in Sri Lanka is located Nugegoda, Sri Lanka. The objective of the study was to identify the research research publications of the University of Sri Jayewardenepura at international level with the data collected from t database-Scopus. Quantitative methodological approach was taken, based on bibliometric analysis. The process of article selection was as follows: Affiliation - ' University of Sri Jayewardenepura’ Publication year - 'up to December 2012'. Results of this study show entirely, 420 papers were published during the study period, including 07 document types. Among them, there were 354 articles. Highest numbers of researches were published during the years 2012 and 2008 respectively. Article form most widely used followed by conference papers and english language prefferd to be frequent medium of communication. The most productive authors are Jansz, E.R., Malavige, G.N. and Wickremasinghe, A.R. The output of Medicine was found to be larger than other subjects, which was followed by Agricultural and Biological sciences and Chemistry. Journal of the National Science Foundation of Sri Lanka leads at the first rank of journal title for scientists to publish their research findings. The suggestion of this research is to encourage more research publications in the field of Arts and Humanities and Social sciences at international level.
Keywords: Bibliometrics; Scholarly communication; Higher education; Sri Lanka